The Effect of Resistance Training on the Development of Upper Limb Explosive Power in Amateur Male Volleyball Players - Naseem Ullah; Sardar Nasir Sohail Khan; Sadia Mehreen (`, 2025)
This study aimed to examine the impact of resistance training on the explosive power of the upper limbs in amateur male volleyball players. A pre-test and post-test research design was employed with a total of 30 college-level athletes, divided equally into experimental (n = 15) and control (n = 15) groups. The experimental group followed a structured 10-week resistance training program, conducted three times per week, while the control group continued with their routine activities. The training sessions included a six-minute warm-up and five resistance exercises (medicine ball overhead throws, push-ups, plyometric push-ups, push press, and medicine ball chest pass), specifically targeting upper limb explosive power. Pre-test results indicated no significant difference between groups, confirming baseline equivalence. However, post-test analysis revealed a significant improvement in explosive power among the experimental group compared to the control group. Paired samples tests further confirmed that only the experimental group demonstrated meaningful progress. These findings highlight the effectiveness of resistance training in enhancing upper limb explosive power, which plays a critical role in improving volleyball performance. Keywords: Resistance training, explosive power, upper limbs, volleyball players, experimental study